Дисциплінарна відповідальність : теоретичний аналіз - Форманюк, Вікторія Василівна; Форманюк, Виктория Васильевна; Formanjuk, V. (My University, 2010)
In the article legal nature of disciplinary responsibility is analysed in positive and subzero aspects. The author of the article determines the general signs of disciplinary responsibility as a type of legal and social responsibility. The author of the article offers the vision of concept of disciplinary responsibility.
Форманюк В. В. Дисциплінарна відповідальність : теоретичний аналіз / // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С. 191-196.
Keywords: дисциплінарна відповідальність; забезпечення трудової дісципліни; дисциплінарний вплив; дисциплинарная ответственность; обеспечение трудовой дисциплины; дисциплинарное влияние; disciplinary responsibility; ensure labor discipline; disciplinary influence